Dialog Antar Umat Beragama dan Pilar Kerukunan di Indonesia: Konsep Tri Kerukunan Umat Beragama dan Relevansinya - Bayduri Dinanti Nasution; Putri Sri Rejeki; Herviani Herviani; Dilla Syafitri; Muhammad Aziz; Muhammad Arif Hasibuan (Pusat Riset dan Inovasi Nasional, 2024)
Amid rising challenges of intolerance, social polarization, and the strengthening of exclusive religious sentiments, interreligious dialogue has become a strategic instrument for nurturing diversity and reinforcing national harmony. This study examines how interreligious dialogue contributes to strengthening the pillars of harmony as outlined in the concept of the Tri Kerukunan Umat Beragama (Three Pillars of Religious Harmony). It also explores the extent to which this concept remains relevant and effective in addressing the current dynamics of religious diversity in Indonesia. The purpose of this research is to analyze the role of dialogue as a mechanism of cross-faith communication in fostering mutual understanding, cultivating respect for differences, and promoting harmonious social relations within a pluralistic society. Using a qualitative approach through a comprehensive literature review, this study investigates various scholarly works related to interfaith dialogue, religious harmony, and Indonesia’s socio-religious landscape.The findings indicate that interreligious dialogue functions not only as a means of resolving differences and preventing conflict but also as a transformative space that strengthens trust, cooperation, and solidarity across religious communities. Thus, dialogue remains a crucial pillar in achieving sustainable and inclusive religious harmony in Indonesia, although it requires